Design of Measurement and Control System of Composite Fast Transfer Switch Based on PLC - ZHANG Hong-yi; WEI Xin-lao (Journal of Harbin University of Science and Technology, 2017)
The fast transfer switch gets more extensive application in the power supply system along with the raising of power supply requirement for continuity and reliability in the sensitivity loads such as in airport，military place，hospital and large scale industrial production line． Therefore it is important that how to make fast transfer switch run safely and reliably． The paper expatiated the structure and principle of a fast transfer switch based on mechanical and electronic compound technology，and，according to the basic requirement and the characteristic of the fast transfer switch，a PLC mastered measuring and controlling system has been designed to raise the operation reliability of the fast transfer switch．